4(2x+1)-3(x+3)=5(x-2)

Simple and best practice solution for 4(2x+1)-3(x+3)=5(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+1)-3(x+3)=5(x-2) equation:


Simplifying
4(2x + 1) + -3(x + 3) = 5(x + -2)

Reorder the terms:
4(1 + 2x) + -3(x + 3) = 5(x + -2)
(1 * 4 + 2x * 4) + -3(x + 3) = 5(x + -2)
(4 + 8x) + -3(x + 3) = 5(x + -2)

Reorder the terms:
4 + 8x + -3(3 + x) = 5(x + -2)
4 + 8x + (3 * -3 + x * -3) = 5(x + -2)
4 + 8x + (-9 + -3x) = 5(x + -2)

Reorder the terms:
4 + -9 + 8x + -3x = 5(x + -2)

Combine like terms: 4 + -9 = -5
-5 + 8x + -3x = 5(x + -2)

Combine like terms: 8x + -3x = 5x
-5 + 5x = 5(x + -2)

Reorder the terms:
-5 + 5x = 5(-2 + x)
-5 + 5x = (-2 * 5 + x * 5)
-5 + 5x = (-10 + 5x)

Add '-5x' to each side of the equation.
-5 + 5x + -5x = -10 + 5x + -5x

Combine like terms: 5x + -5x = 0
-5 + 0 = -10 + 5x + -5x
-5 = -10 + 5x + -5x

Combine like terms: 5x + -5x = 0
-5 = -10 + 0
-5 = -10

Solving
-5 = -10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2445/2200 | | 2x+3(x-2)-3(x-6)=0 | | 5x+5=3(5x-5)-20x | | 6-12x/4-7=14 | | 5x+130=8x+181 | | 5+2*10=n | | 10s/5=10 | | (2x-1)(2x-3)= | | (x-6)(2x+3)= | | X^5x=100 | | 5+2n=-5 | | 4x=(70-x) | | x+5(5x-1)=99 | | 10y+9-2y=4y+3y+12 | | x-.5x=1000 | | 6(7x-6)+8=-154 | | 2x-5=(x-5) | | (1.3_0.06)/0.8 | | -31=4w+1 | | 0=x^5+2x^3+x | | 7-6a=-5-3(a-5) | | N+28=2N+16 | | 12=3(v-6) | | 6-3w=12 | | 2x-7=15-5x | | 5x-3=8x-21 | | 12x+33=x | | 7(x-7)=-4-16 | | -6.3m+2.7m= | | 0.75x+37-2.75=3(4+x) | | 5x-4=8x+12 | | 0.6x=0.5 |

Equations solver categories